Bayesian statistics : an introduction - Lee, Peter M. (Chichester, West Sussex ; Hoboken, N.J., 2012)
'- Presents extensive examples throughout the book to complement the theory presented.Includes significant new material on recent techniques such as variational methods, importance sampling, approximate computation and reversible jump MCMC'--
Includes bibliographical references and index.
Buku Bacaan Asas Fakulti
Keywords: Bayesian statistical decision theory